Going corporate a Geek's guide - Kadre, Shailendra (Apress, 2011)
Going Corporate: A Geek's Guide shows technology workers how to gain the understanding and skills necessary for becoming an effective, promotable manager or sought-after consultant or freelancer. Technology professionals typically dive deeply into small pieces of technology like lines of code or the design of a circuit. As a result, they may have trouble seeing the bigger picture and how their work supports an organization's goals. But ignoring or dismissing the business or operational aspects of projects and products can lead to career stagnation. In fact, understanding the larger business environment is essential for those who want a management job, a consulting gig, or to one day start a business. It's also essential for those who have been promoted and find themselves flailing for lack of a business education. Going Corporate: A Geek's Guide to the rescue! This book is designed to help readers gain management skills, insight, and practical understanding of essential business and operational topics. Readers will learn to develop project and program management skills, deliver service efficiently and improve processes, implement governance, analyze financial statements, and much more. After reading this book, technology professionals will understand such things as enterprise architecture, IT operations management, strategic and financial management and how each relates to the others. Detailed case studies help cement an understanding of how an IT organization and its workers succeed in the 21st century. This book: Illustrates how pieces of the business puzzle fit together to form a robust enterprise Prepares readers to get promoted into management Explains the key management skills and knowledge required for a successful IT